Controlling the properties of graphene produced by electrochemical exfoliation. (29th July 2015) - Hofmann, Mario; Chiang, Wan-Yu; D Nguyễn, Tuân; Hsieh, Ya-Ping
Abstract: The synthesis of graphene with controllable electronic and mechanical characteristics is of significant importance for its application in various fields ranging from drug delivery to energy storage. Electrochemical exfoliation of graphite has yielded graphene with widely varying behavior and could be a suitable approach. Currently, however the limited understanding of the exfoliation process obstructs targeted modification of graphene properties. We here investigate the process of electrochemical exfoliation and the impact of its parameters on the produced graphene. Using in situ optical and electrical measurements we determine that solvent intercalation is the required first step and the degree of intercalation controls the thickness of the exfoliated graphene. Electrochemical decomposition of water into gas bubbles causes the expansion of graphite and controls the functionalization and lateral size of the exfoliated graphene. Both process steps proceed at different time scales and can be individually addressed through application of pulsed voltages. The potential of the presented approach was demonstrated by improving the performance of graphene-based transparent conductors by 30times.